Trophic interactions and metal transfer in marine ecosystems driven by the Peruvian scallop Argopecten purpuratus aquaculture. Issue 2 (16th June 2021) - Loaiza, Iván; De Boeck, Gudrun; Alcazar, Juan; Campos, Diego; Cárdenas‐Alayza, Susana; Ganoza, María; Gómez‐Sanchez, Muriel; Miglio, María; De Troch, Marleen
Abstract: This study investigates the trophic interactions and As and Cd transfer along seven marine ecosystems in Peru. Five of these ecosystems are driven by aquaculture of the Peruvian scallop Argopecten purpuratus . A southward increased gradient of δ 15 N was observed among the three examined regions along the Peruvian coast. The stable isotope analysis in R (SIAR)‐stable isotope mixing models helped to clarify the feeding ecology of A. purpuratus and its important predators (e.g., Bursa ventricosa, Romaleon setosum ). The food items of A. purpuratus can be ranked in decreasing order of importance: seston > sediment > particulate organic matter (POM) > brackish‐and‐fresh water POM input, while A. purpuratus itself was found to be the main prey item for predators. The highest trophic magnification factors (TMFs) were 1.46 and 1.07 for As and Cd, respectively, and were both found at the location in front of the Illescas Reserve Zone (northern Peru). Metal biomagnification and non‐biomagnification effects were found in the Peruvian marine food webs, but A. purpuratus always fitted the trophic metal magnification or bio‐dilution regression model as intermediate consumer and/or prey. The TMFs and linear metal relationships implied that As contamination is a serious concern in marine ecosystems in Peru.